UJI AKTIVITAS EKSTRAK ETANOL KULIT BATANG PURNAJIWA TERHADAP JAMUR Fusarium oxysporum f. sp. lycopersici - Selviana Dismiyanti Daus; Putu LY Sapanca; Putu Eka Pasmidi Ariati; Ramdhoani (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Purnajiwa plant (Kopsia arborea Blume.) is a type of plant from the Apocynaceae family that has the potential as a source of natural antioxidants. Parts purnajiwa plant contain many compounds with antimicrobial properties. These co mpounds can be obtained from roots, bark, seeds, shoots, leaves, flowers and fruit. This research is a laboratory experimental study using a Completely Randomized Desing (CRD) with 6 treatments. The treatment was repeated 3 times with various concentrations of control, 5%, 10%, 15%, 20% and 25%. The material used in this research is the extract of the bark of the stems of Purnajiwa, which is macerated with ethanol as a solvent to produce a thick extract and then tested for antibacterial activity on the fungus Fusarium oxysporum f. sp. lycopersici parameters observed were the inhibition test on colony growth in vitro. Data analysis used a single ANOVA variance. The results showed that the bark extract of the Purnajiwa's stem had the ability to inhibit the growth of the fungus Fusarium oxysporum f. sp. lycopersici on the seventh day of treatment. The most effective concentration in inhibiting the growth of Fusarium oxysporum f. sp. lycopersici was present at a concentration of 20% with the highest average value of 90,17mm, with a percentage of 88,48%.